Liberalization of Financial Services and Performance of Commercial Banks in Algeria: An Empirical Study (1998 – 2012) - Benahmed-Daho, Rachida; Bouteldja, Abdelnacer; Bendob, Ali (International Journal of Economics and Financial Issues, 2015)
The banking system is facing deep and varied challenges due to financial openness and bank liberalization which both call for the removal of all restrictions and barriers on banking activities, as well as for a competition between foreign and local banks, which has increased in recent years. The aim of this paper is to investigate the impact of financial liberalization on banking efficiency in Algeria. Using three varieties of a panel data regression model on a sample of 10 Algerian commercial banks (public and private) for the period during 1998-2012. Our results show a negative and significant impact of financial liberalization on Algerian banking performance. Keywords: financial liberalization; Algerian commercial banks; performance; panel data. JEL Classification: G21; G23: L25.